2016
DOI: 10.1186/s40545-016-0075-5
|View full text |Cite
|
Sign up to set email alerts
|

Prescription medicine sharing: exploring patients’ beliefs and experiences

Abstract: BackgroundPrescription medicine sharing has been defined as the lending of medicines (giving prescription medicines to someone else) or borrowing of medicines (being given and using a medicine prescribed for another person). This qualitative study explored the views of patients, to elicit information regarding factors influencing medicine sharing behaviours, their experiences of the consequences of prescription medicine sharing, and their risk assessment strategies when deciding to share.MethodsOne-on-one, fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
51
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(57 citation statements)
references
References 35 publications
(96 reference statements)
6
51
0
Order By: Relevance
“…Conversely, medicines to treat heart problems, high blood pressure and diabetes were the top three medicines that study participants believed unsafe to be shared. This finding is consistent with previous research reports . In general, patients may have their own unique ways of evaluating the risks of sharing certain medicines.…”
Section: Discussionsupporting
confidence: 92%
“…Conversely, medicines to treat heart problems, high blood pressure and diabetes were the top three medicines that study participants believed unsafe to be shared. This finding is consistent with previous research reports . In general, patients may have their own unique ways of evaluating the risks of sharing certain medicines.…”
Section: Discussionsupporting
confidence: 92%
“…In line with earlier survey reports, in this study a wide range of medicines were reported to be shared. The findings regarding the types of shared medicines are also largely consistent with our previous qualitative study with patients: e.g. antibiotics, opioid analgesics, acne medicine, and steroid creams were reported to be commonly shared by both types of interviewees.…”
Section: Discussionsupporting
confidence: 88%
“…Fourth, although great efforts were made to increase the participation of community practitioners, particularly general practitioners, community practitioners were underrepresented in this study. Nonetheless, many of the findings reported here were echoed in our previous qualitative study with patients …”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations